Trust in Automated Writing Evaluation (AWE): Multiple case study on feedback engagement and literacy - Drajati, Nur Arifah; Handayani, Anis (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
Artificial Intelligence (AI) for educational purposes has recently been a research interest. Specifically for academic writing, AI-based feedback, often called automated writing evaluation (AWE), is an essential aspect to support students"™ writing. However, despite its popularity, the trust in AWE, which potentially contributes to the students"™ writing improvement, has been explored on a limited basis. Hence, this multiple case study attempts to examine the trust in AWE and how this trust influences feedback engagement and literacy. Of 42 students joining a writing class, a total of 4 undergraduate students were involved to explore this issue. Considering the Indonesian government's policy to conduct online learning amidst the COVID-19 pandemic era, classroom observation, stimulated recalls, and semi-structured interviews were conducted virtually via Zoom meetings to gather the data. Results show that the students' trust in AWE varied, indicated by their varied responses to AWE. Furthermore, their trust in AWE only affects the behavioral aspect, excluding the cognitive and affective aspects. Meanwhile, in feedback literacy, their trust only affected the aspect of appreciating the feedback. These findings imply that educators should pay interest to students' trust in AWE since it, in some ways, influences improvement of their feedback engagement and literacy.